Insights into Knowledge, Attitude and Perception about Dental Ergonomics and Work-Related Musculo Skeletal Disorders (MSD) among Dental Professionals at Chengalpet District, Tamil Nadu, India: A cross-sectional study (International Journal of Occupational Safety and Health, 2022)
Introduction: Despite all modern technological advances, dentistry is a profession still being affected by various musculoskeletal disorders, because of their prolonged working hours and difficult postures. Hence, this study was undertaken to assess the basic knowledge, attitude and practice of dental ergonomics during routine dental procedures among dental professionals and the second aim of the study focused on knowledge, attitude and practice of dental ergonomics by gender.Methods: A cross-sectional study was conducted among 203 dental professionals from January 2021 to February 2021. A structured questionnaire consisting of 15 questions was administered. Descriptive analysis of demographic variables was done and knowledge, attitude and perception scores were performed using the chi-square test.Results: Among the 203 participants, a considerable majority of the participants which is about 75.9% (male: 71.1% and female: 79.6%) reported that they have awareness of dental ergonomics. There were no statistically significant differences between males and females regarding knowledge score of p=1.280. About 46.4% of participants (male: 54.3 % and female: 43.9%), complained of neck pain followed by 44.3% (male 41.3% and female 45.2%) complained of back pain. About 58.6% reported that the pain was caused strictly because of improper posture and non-ergonomically designed equipment. The difference between the gender variations was statistically significant regarding perception about dental ergonomics (p=0.001*)Conclusion: Dental professionals have considerable awareness of ergonomics in dental practice. The current study highlights the situation of ergonomics in dental practice in the form of knowledge, attitude, and practices.